A comparison of King vision video laryngoscope with CMAC D-blade in obese patients with anticipated difficult airway in tertiary hospital in India - Randomized control study - Raj Sahajanandan; Anity Singh Dhanyee; Arun Kumar Gautam (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: This randomized control trial was conducted to compare two video laryngoscopes in obese patients with anticipated difficult airway. Video laryngoscopes have shown to be beneficial in many difficult airway scenarios including obesity. Many studies have shown that even though the glottic view is better, it takes longer to negotiate the endotracheal tube. We proposed to compare CMAC D-blade with King vision-channeled blade for intubating obese patients with anticipated airway difficulty. We hypothesized that channeled scope may be superior as once visualized, tube could be easily negotiated. This would be reflected by time taken for the glottis visualization, time taken for intubation, incidence of complications, and hemodynamic stability. Material and Methods: Sixty-three patients who fulfilled inclusion criteria were enrolled after informed consent. Based on the computer-generated randomization, they were assigned to group 1 (King vision laryngoscope - KVL) and group 2 (CMAC D-blade). All anesthetists who intubated, performed 20 intubations with both video laryngoscopes on manikin before performing the study case. The parameters analyzed were time to visualize the glottis, time to successful intubation, and intubation-related hemodynamic variations and complications. Results: The mean time taken to visualize the glottis with KVL was 12.93 s compared to 10 s with CMAC D-blade (P value 0.12). Time taken to intubate was 50.04 s with KVL compared to CMAC D-blade which took 46.93 s (P value 0.64). KVL had a complication rate of 20.7% compared to 3.1% with CMAC D-blade (P value 0.04). Conclusion: There was no statistically significant difference in time to visualize the glottis and intubation between KVL and CMAC D-blade. But there was a high incidence of complications with KVL.